Feeding on epibenthic zooplankton by Long‐tailed Ducks: patch structure, profitability, and food web implications - James R. Lovvorn (Wiley, 2021)
Abstract Models of the trophic needs and impacts of mobile predators in food web networks typically do not consider interactions between prey dispersion and threshold prey densities needed for profitable foraging. As a result, the biomass of predators that can be supported, or direct and indirect impacts of those predators on other food web components, may be poorly estimated. In Simpson Lagoon on the U.S. Arctic coast, epibenthic amphipods and especially mysid shrimp comprised most of the diets of fish, and of Long‐tailed Ducks (Clangula hyemalis) which strongly dominated prey consumption. Based on mean prey densities and gross estimates of prey biomass consumed, earlier studies estimated that continuous immigration of mysids into the lagoon was needed to support the predators. Comparison of variances from net samples vs. different probability density functions (PDFs) around reported means indicated that prey were not normally distributed, and instead occurred in patches with a skewed and wide range of densities. We used the functional response of captive Long‐tailed Ducks eating mysids, and a foraging energetics model, to identify minimum prey densities these diving ducks needed to feed profitably. Based on PDFs that assumed prey densities in all 1‐m2 cells (patches for single feeding dives on potential mysid swarms) were independent, we simulated prey grids with slightly skewed to highly skewed distributions for the reported sample means. Results showed that the greater the range of patch densities, the smaller the fraction of prey biomass that was profitably available to the ducks, thereby increasing the requisite immigration of mysids. Consumption by ectothermic predators further decreased prey available and advanced the date and increased the amount of mysid influx required. The models also showed that the birds had to seek areas with non‐independent clusters of high‐density feeding patches as prey declined in late summer. Thus, spatially continuous measures of patch structure over larger scales are needed to estimate the fraction of prey that is functionally available. Our study emphasizes that when estimating trophic needs and impacts of mobile endothermic predators, simple means of prey density can be misleading, owing to interactions of prey patch structure with profitability thresholds.